1998
DOI: 10.1007/s004200050271
|View full text |Cite
|
Sign up to set email alerts
|

Measured exposures by personal monitoring for respirable suspended particles and environmental tobacco smoke of housewives and office workers resident in Bremen, Germany

Abstract: The most highly exposed workers, both living and working with smokers, would potentially inhale over 20 cigarette equivalents (CE) per annum as based on the upper decile levels. Housewives living with smokers could inhale up to 11 CE per annum as based on the upper decile levels. Locations outside the workplace, including the home, contribute most to overall RSP and ETS particle exposure. Consideration should be given to extending the personal monitoring period in cities where levels appear to be quite low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…The range of PBZ NIC air sample concentrations (0.58-17 μg/m 3 ) is comparable to past studies of workers in smoking environments [Phillips et al 1998;Jenkins and Counts 1999], including one study of casino dealers [Trout et al 1998]. Likewise, the range of area air sample concentrations of NIC was comparable to data reported by Trout et al [1998], who reported PBZ NIC concentrations between 6 and 15 μg/m 3 for casino dealers.…”
Section: Environmental Monitoringsupporting
confidence: 86%
“…The range of PBZ NIC air sample concentrations (0.58-17 μg/m 3 ) is comparable to past studies of workers in smoking environments [Phillips et al 1998;Jenkins and Counts 1999], including one study of casino dealers [Trout et al 1998]. Likewise, the range of area air sample concentrations of NIC was comparable to data reported by Trout et al [1998], who reported PBZ NIC concentrations between 6 and 15 μg/m 3 for casino dealers.…”
Section: Environmental Monitoringsupporting
confidence: 86%
“…However, sidestream smoke, after mixing with aged exhaled mainstream smoke, is diluted massively by room air before non-smokers inhale it. Smoke constituent levels in tissues of non-smokers are very much lower than in smokers, studies using cotinine typically indicating a relative exposure factor between 0.06% and 0.4% [33][34][35] , with studies using particulate matter indicating a lower factor of 0.005% to 0.02% [36][37][38][39][40][41][42][43][44] . Though an effect of ETS on COPD risk is plausible, it is difficult to establish this with certainty, as a threshold is a logical possibility.…”
Section: Introductionmentioning
confidence: 99%
“…Phillips et al (1996Phillips et al ( , 1997 have reported on the nicotine exposure and salivary cotinine levels of 190 nonsmokers in Stockholm, Sweden, and 188 nonsmokers in Turin, Italy. A recent series of manuscripts by these same authors has reported nicotine exposures and salivary cotinine levels for subjects in the cities of Lisbon, Bremen, and Paris (Phillips et al, 1998a(Phillips et al, , 1998b(Phillips et al, , 1998c.…”
Section: Comparison Of Salivary Cotinine Levels and Nicotine Exposurementioning
confidence: 99%
“…While many studies have examined its relationship to some indicators of ETS exposure (time spent around smokers, number of cigarettes observed, number of smokers in one's residence, etc.) (e.g., Jenkins et al, 1992;Delfino et al, 1993;Emmons et al, 1994;Rebagliato et al, 1995;Thompson et al, 1995;Tunstall-Pedoe et al, 1995;Emmons et al, 1996), few studies have provided an assessment in nonsmokers of cotinine levels vs. airborne nicotine (e.g., Proctor et al, 1991;Marbury et al, 1993;Ogden et al, 1993;Bergman et al, 1996;Phillips et al, 1996Phillips et al, , 1997Phillips et al, , 1998aPhillips et al, , 1998bPhillips et al, , 1998c. Nicotine is the primary precursor to cotinine (Curvall et al, 1990;Byrd et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation